Observatório da seguridade social: Uma proposta - Luciana Jaccoud (Instituto de Pesquisa Econômica Aplicada (IPEA), 2025)
– This work presents a proposal for a Social Security Observatory, with the objective of working on the production and dissemination of knowledge related to social security, with an emphasis on topics that jointly mobilize the action of sectoral policies in health, social security and social assistance. The proposal is based on the recognition that, in the field of social security, public and social problems mobilize a joint field of responsibilities. Through the production of information, indicators, systematic monitoring, analyses and studies, the Social Security Observatory would favor the improvement of more articulated forms of care. It would contribute to the elaboration of common diagnoses and the construction of shared interpretative frameworks, in addition to supporting dialogue in favor of greater alignment on topics, intervention strategies and intersectoral institutional arrangements.
Keywords: I31; I38; 330; social security; social observatory; social protection; macrosectoral; intersectionality